The influence of the composition of mixed Karoo vegetation on the grazing habits of Merino and Dorper wethers - Roux, Francis Augustus (Rhodes University, Faculty of Science, Botany Department, 1994)
The primary objective of this research project was to determine whether area-selective grazing, by Dorper and Merino wethers, took place in small grazing camps as governed by differences in vegetal cover. The main research techniques employed were the descending-point method for the determination of botanical composition, sub-division of the camps into gridblocks to trace sheep movement in relation to vegetation patterning, fistulated animals to determine diet selection, the electronic theodolite for micro-topography, and few minor techniques. The result have shown that area- patch- and species selective grazing are prevalent in small grazing camps under "normal" stocking densities, and that different breeds of stock (Merino and Dorper sheep) have different grazing patterns and diet selection . Climax and sub-climax areas were those primarily select ed for grazing. There is little or no correlation between botanical composition and diet selected as per fistula ted animal. The average distances travelled by Dorpers and Merinos was 2 km / day and 3.1 km/day respectively. Plant phenology did not have a detectable influence in the choice of diet.
Keywords: Grazing -- South Africa -- Karoo; Sheep -- Feeding and feeds; Dorper sheep -- South Africa; Merino sheep -- South Africa